Mitochondrial Proteins Coded by Human Tumor Viruses - Cavallari, Ilaria; Scattolin, Gloria; Silic-Benussi, Micol; Raimondi, Vittoria; D'Agostino, Donna M.; Ciminale, Vincenzo (Frontiers in Microbiology, 2018)
Viruses must exploit the cellular biosynthetic machinery and evade cellular defense systems to complete their life cycles. Due to their crucial roles in cellular bioenergetics, apoptosis, innate immunity and redox balance, mitochondria are important functional targets of many viruses, including tumor viruses. The present review describes the interactions between mitochondria and proteins coded by the human tumor viruses human T-cell leukemia virus type 1, Epstein-Barr virus, Kaposi's sarcoma-associated herpesvirus, human hepatitis viruses B and C, and human papillomavirus, and highlights how these interactions contribute to viral replication, persistence and transformation.